Approaches of News Translation and Its Teaching Guidance – Taking the Translation Practice of the Economist as an Example - Ji, Yongyi (Journal of Theory and Practice of Social Science, 2023)
With the advancement of science and technology, news is more and more closely related to human daily life. At the moment when news constantly breaks the communication barrier, news translation has also received more attention. This paper selects news from The Economist for translation practice, analyzes the language characteristics of news translation, and summarizes translation strategies. As an information text, news translation has dual attributes of functionality and literariness. Translators need to make cultural compensation when translating, and use translation techniques such as voice shifting, four-character structure, and amplification to fully convey the information and style of news texts.